The body composition phenotype of Irish adults aged 18–81 years. (May 2016) - Toomey, C.; Leahy, S.; McCreesh, K.; Coote, S.; Jakeman, P.
Abstract Background Regional distribution of adiposity and lean tissue mass are predictors of health risk that cannot be defined by body mass index but can be attained by dual-energy X-ray absorptiometry (DXA). Age and sex-related adult ranges of whole-body and regional adiposity and lean tissue are not available for Irish men and women. Aims The aim of this study was to construct a DXA-based body composition profile of Irish adults, focusing on age- and sex-related difference in total and regional adiposity and lean tissue mass. Methods The study population comprised a convenience sample of 1606 participants, aged 18–81 years participating in the University of Limerick Body Composition study. Data were analysed to construct stature-normalised indices of body fat mass (BFMI), site-specific visceral adiposity, lean tissue mass (LTMI) and appendicular lean tissue mass (ALTMI). Results Compared to the young adult (18–29 years), BFMI was higher in women (p < 0.001) but plateaued in men aged >50 years. For men, age-related difference in LTMI was not evident but ALTMI was significantly lower in those >50 years. For women, there was evidence of significantly lower LTMI with advancing age and, similar to men, significantly lower ALTMI in those >50 years. Conclusions These data provide an insight into the age-related anthropometric phenotype of Irish adults. Centile data have been constructed that provide informative data of the age and sex-specific range of adiposity and lean tissue mass. These data may assist in identification of those at risk of aberrant, body composition-related disease.